Interpretation Bias Modification Versus Progressive Muscle Relaxation for Social Anxiety Disorder: A Web-Based Controlled Trial. Issue 1 (January 2020) - Cougle, Jesse R.; Wilver, Natalie L.; Day, Taylor N.; Summers, Berta J.; Okey, Sarah A.; Carlton, Corinne N.
Abstract: Computerized interpretation bias modification (IBM) programs show promise for the treatment of anxiety disorders, though they have rarely been compared to active treatments. The goal of the present study was to compare the efficacy of IBM to progressive muscle relaxation (PMR) for the treatment of social anxiety disorder (SAD). Sixty-four participants with SAD were recruited from across the United States and randomly assigned to 8 internet-delivered twice-weekly sessions of IBM or PMR. Participants were administered assessments of primary symptom outcomes and interpersonal suicide risk factors at posttreatment and 3-month follow-up. IBM led to significantly lower negative interpretation bias than PMR at posttreatment but not follow-up. Both conditions experienced comparable reductions in social anxiety from pretreatment to follow-up (IBM d = 1.37, PMR d = 1.28). They also experienced significant reductions in depression and general anxiety that did not differ from one another. Additionally, IBM led to greater reductions in thwarted belongingness than PMR at posttreatment but not follow-up. Overall, these findings suggest IBM is not more effective than PMR for reducing social anxiety, though there was some evidence of its superiority in decreasing suicide risk. Limitations and directions for future research are discussed. Highlights: We compared interpretation bias modification to progressive muscle relaxation for social anxiety Both treatments were delivered online and had very low attrition Both treatments were associated with substantial, equivalent improvements in social anxiety